Pelatihan Penerapan 3J untuk Mengendalikan Kadar Gula Darah bagi Penderita Diabetes Melitus - Fathurrahman; Sajiman; Magdalena (UPPM Poltekkes Kemenkes Banjarmasin, 2024)
Type 2 diabetes mellitus (DM) is a significant global health issue, including in Indonesia. Effective DM management relies heavily on patients’ knowledge and skills in managing diet and lifestyle. However, public awareness, especially in rural areas, remains low. This study aims to improve the knowledge and skills of DM patients in Melayu Village, Martapura Timur District, through a nutrition education program and practical application of meal regulation (3J: type, amount, and schedule of meals). The method used includes a two-day education program, counseling, monitoring, and evaluation of blood sugar levels. A total of 40 participants, consisting of 39 women and 1 man, participated in this activity. The training included lectures, discussions, and meal portioning practices. Measurements were taken before and after the training, including pretests, posttests, and blood sugar examinations. Results showed a significant improvement in participants' knowledge, with the average pretest score increasing from 69.2 to 78.1 on the posttest (p<0.05). Additionally, participants’ average blood sugar levels decreased from 219.8 mg% to 189.8 mg% (p<0.05) after the training. In conclusion, a well-designed nutrition education program can enhance DM patients' knowledge and skills in disease management and reduce their blood sugar levels. Ongoing education and monitoring are necessary to support successful DM management in the community.